2022
DOI: 10.1002/anie.202214838
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Azaarylethynyl Tertiary Alcohols by Chiral Brønsted Acid Catalysed Phosphine‐Mediated Deoxygenation

Abstract: A chiral Brønsted acid catalysed phosphinemediated deoxygenation protocol is reported. This metal-free method provides a precise kinetic resolution platform for azaarylethynyl tertiary alcohols, which are a broad category of biologically and synthetically important azaarene derivatives. In addition to providing an efficient method for the first asymmetric preparation of these tertiary alcohols, the strategy facilitates the construction of azaaryl-functionalized allenes with good to excellent enantioselectiviti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Allenes have attracted significant attention 1 in the fields of natural products, 2 modern organic synthesis, 3,4 medicinal chemistry, 5 and materials science, 6 and thus, much attention has been paid to the development of new methodologies for the syntheses of allenes from readily available starting chemicals. 7 Among them, a two-component reaction between readily available alkynes with an appropriate propargylic leaving group and organometallic reagents has been developed as a straightforward method for the syntheses of allenes 8 (Scheme 1a). We envisioned a new concept of Pd-catalyzed reaction of readily available 2-alkynyl-1,4-diol dicarbonate with an organometallic reagent and a nucleophile for allene synthesis (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Allenes have attracted significant attention 1 in the fields of natural products, 2 modern organic synthesis, 3,4 medicinal chemistry, 5 and materials science, 6 and thus, much attention has been paid to the development of new methodologies for the syntheses of allenes from readily available starting chemicals. 7 Among them, a two-component reaction between readily available alkynes with an appropriate propargylic leaving group and organometallic reagents has been developed as a straightforward method for the syntheses of allenes 8 (Scheme 1a). We envisioned a new concept of Pd-catalyzed reaction of readily available 2-alkynyl-1,4-diol dicarbonate with an organometallic reagent and a nucleophile for allene synthesis (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Zhou and colleagues reported the enantioselective CuI-catalyzed azide–alkyne cycloaddition (CuAAC) of racemic tertiary propargylic alcohols (Scheme b, eq 3) . Very recently, the Jiang group reported chiral Brønsted acid-catalyzed phosphine-mediated deoxygenation of azaarylethynyl tertiary alcohols . Despite this breathtaking progress, there is still room for the development of new catalytic systems for accessing optically active acyclic tertiary propargylic alcohols.…”
mentioning
confidence: 99%
“…On the other hand, propargylic alcohols are easily available and versatile building blocks in organic synthesis due to the presence of two functionalities . Recently, our group have developed a series of transition-metal-catalyzed reactions of propargylic alcohols: , we reported that under the catalysis of Rh­(III), the C–H functionalization of arenes with tertiary propargylic alcohols afforded tetra-substituted allenes (Scheme a, eq 1) . In addition, Rh 3+ /Ag + -cocatalyzed reaction of propargylic alcohols with boronic acids would afford allylic alcohols (Scheme a, eq 2) .…”
mentioning
confidence: 99%